"Preparation and curing kinetics of “bottlebrush-like structure” green bio-based ultra-low-temperature polyfarnesene nanocomposites" - WU Ming-li, LI Yong-xu, CAO Lan?鄢 (Hecheng xiangjiao gongye)
"Based on the requirements of dual-carbon strategy and the major needs of sustainable development, it was of great significance to develop green and environmentally-friendly bio-based rubbers. However, it was difficult for existing rubber materials to simultaneously meet the requirements of low-temperature resistance and excellent dynamic performance, which greatly limited its application in special fields at low temperature. To solve this problem, the bio-based acyclic sesquiterpene compound, trans-β-farnesene was autonomously synthesized by bio-fermentation in our laboratory. As a versatile monomer, trans-β-farnesene had a special structure of long side chain monosubstitution, which could be genetically edited from the source to form a “bottlebrush-like” polymer with a regular structure. In this work, hydroxyl-terminated polyfarnesene (HTPF) was synthesized by free-radical solution polymerization, and enhanced HTPF-based polyurethane elastomers (HTPF-PU) was prepared using HTPF as soft segment and functionalized graphene oxide (GO) modified with isophorone diisocyanate (IPDI) as functional filler by one-step process for the first time, which allowed the isocyanate groups on modified graphene oxide (iGO) and the hydroxyl groups in HTPF to form covalent bonds to prepare nanocomposites with a strong interfacial bonding effect, as shown in Fig 1. The results showed that the layer spacing was enlarged from 1.006 nm to 1.075 nm after modification. In the range of 100-700 ℃, the mass loss fraction of GO was 48.22% and that of iGO was 58.49%. The grafting modification was successful and the thermal stability of iGO was improved. In addition, the result of the infrared spectroscopy carbonyl peak fitting for iGO/HTPF-PU nanocomposites showed increasing hydrogen bonding up to 87.2% compared to pure HTPF-PU, indicating better dispersion of iGO in the matrix. iGO/HTPF-PU nanocomposites had excellent thermal properties. With the increase in iGO fill amount, the glass transition temperature of the nanocomposites decreased gradually and reached as low as -82 ℃, which indica-ted that the nanocomposites had excellent low-temperature resistance. Finally, the rheological properties and isothermal curing reaction kinetics of the nanocomposites were studied by rheological test. With the curing reaction, the complex viscosity and storage modulus of the nanocomposites increased gradually, and the effect was the best when the iGO fill mass fraction was 0.1%. Based on the Sestak-Berggren model of thermal analysis kinetics, the curing kinetic parameters were solved, including the reaction orders, pre-exponential factor and activation energy, and the curing kinetic equation of the composite, dα/dt=3.667×107exp(-7.514×104/RT)α1.211(1－α)1.164, where α was curing degree, t was curing time, R was molar gas constant and T was curing temperature, was established."